FUNGSI, KATEGORI, DAN PERAN SINTAKSIS KALIMAT PADA PUPUH DURMA DALAM GEGURITAN TIRTA AMERTA - TRISNAWATI, A. A. ARY (S2 Ilmu Linguistik Fakultas Ilmu Budaya Universitas Udayana, 2015)
This article is entitled Function, Category and Role of Sentence Syntaxis in Pupuh Durma in Geguritan Tirta Amerta. The aims of the research ane structures (1) sentence function in pupuh durma, (2) category in pupuh durma, (3) role in pupuh durma, and (4) tree diagram in Syntaxis category. This research uses RRG (Role and Reference Grammar) theory which was introduced by Robert D. Van Valin, Jr. And Randy J. LaPolla (1997). The data in this research is in firm of sentences in Balinese Language in pupuh durma in Geguritan Tirta Amerta. The data in this research is collected by using observation and taking notes. The data that had been noted them translated which leads to finding that syntactically, the sentence 's function in pupuh durma contains subject, predicate /core /nucleus, and object, the subject and object category is noun, while the predicate or nucleus is verb and adjective, and the subject role is as an agent, the object as the patient, and the predicate or nucleus describes activity or situation. Nucleus or the sentence core is on the right side. Artikel ini berjudul “Fungsi, Kategori, dan Peran Sintaksis Kalimat pada Pupuh Durma dalam Geguritan Tirta Amerta”. Penelitian ini bertujuan untuk memahami (1) fungsi kalimat dalam pupuh durma, (2) kategori kalimat dalam pupuh durma, (3) peran kalimat dalam pupuh durma, dan (4) diagram pohon kategori sintaksis kalimat-kalimat dalam pupuh durma. Penelitian ini menggunakan teori RRG (Role and Reference Grammar) yang dikemukakan oleh Robert D. Van Valin, Jr. dan Randy J. LaPolla (1997). Data penelitian ini berupa kalimat-kalimat berbahasa Bali yang ada pada pupuh durma dalam Geguritan Tirta Amerta. Data penelitian ini dikumpulkan dengan metode simak dan catat. Data yang sudah dicatat, kemudian diterjemahkan untuk mengantarkan pada temuan bahwa secara sintaksis, fungsi kalimat dalam pupuh durma mengandung subjek, predikat/inti/nukleus, dan objek. Kategori subjek dan objek adalah nomina, sedangkan predikat atau nukleus adalah kata kerja/verba dan kata sifat/adjektiva, dan peran subjek adalah sebagai pelaku, objek sebagai pasien, dan predikat atau nukleus menggambarkan aktivitas atau keadaan. Nukleus atau inti kalimat berada di sebelah kanan.